2010
DOI: 10.1007/s11064-010-0155-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Nicotine, Alcohol or Their Combination on Cholinergic Markers in the Frontal Cortex and Hippocampus of Rat

Abstract: Acute alcohol (Alc) intoxication has been shown to decrease choline acetyltransferase (ChAT) in the rat brain. The present study extends that finding by examining the effects of nicotine (Nic), Alc, and their combination on ChAT and acetylcholinesterase (AChE) in the frontal cortex and hippocampus of rat. The samples were collected at 30 and 120 min after intraperitoneal administration of saline (0.9%, control), Nic (1 mg/kg), Alc (1 g/kg), and Nic + Alc and analyzed by RT-PCR, Western blot and colorimetry. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These complex behaviors allow for adaptation in response to changes in the environment and are modulated by various neurotransmitters, including the cholinergic system (Logue and Gould 2014 ). Acute ethanol injection shows a dose-dependent effect on ACh release in PFC (Stancampiano et al 2004 ): low intraperitoneal doses of ethanol (0.5 g/kg) increase, while higher doses (1 g/kg) reduce ACh release in the rat PFC (Stancampiano et al 2004 ; Jamal et al 2010 ). These biphasic changes of ACh transmission in the PFC may be of relevance for the bidirectional modulation of working memory by ethanol (Rossetti et al 2002 ; Stancampiano et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…These complex behaviors allow for adaptation in response to changes in the environment and are modulated by various neurotransmitters, including the cholinergic system (Logue and Gould 2014 ). Acute ethanol injection shows a dose-dependent effect on ACh release in PFC (Stancampiano et al 2004 ): low intraperitoneal doses of ethanol (0.5 g/kg) increase, while higher doses (1 g/kg) reduce ACh release in the rat PFC (Stancampiano et al 2004 ; Jamal et al 2010 ). These biphasic changes of ACh transmission in the PFC may be of relevance for the bidirectional modulation of working memory by ethanol (Rossetti et al 2002 ; Stancampiano et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the CTS 100 and CTS 200 groups had reduced enzymatic activity of 88.36% and 59.72%, respectively. Many studies indicated that dysfunction of learning and memory was caused by the degeneration of cholinergic nervous system, and increased AChE activity in the brain could elevate the risk of cognitive disorders (Cohen et al, 2007;Jamal et al, 2010;Srikumar et al, 2004). Tiwari et al (2009) demonstrated that enhanced AChE activity in cerebral cortex and hippocampus of EtOH-treated rats is involved in cognitive deficit.…”
Section: Resultsmentioning
confidence: 99%
“… Karadsheh, Kussie, and Linthicum (1991 ) reported that caffeine inhibited AChE through binding of the N-methyl group of the pyrrolidine ring to AChE. Moreover, it was found that nicotine alone decreased AChE mRNA expression ( Jamal et al, 2010 ). Thus, the oxidative stress, binding of the enzyme, and reduced synthesis may all contribute to the decreased AChE activity induced by caffeine and nicotine, in the present study, thereby augmenting cholinergic activity.…”
Section: Discussionmentioning
confidence: 99%